Patient care pathways under the model of integrating tuberculosis service with general hospitals in China. Issue 11 (8th October 2013) - Wei, Xiaolin; Yin, Jia; Zou, Guanyang; Walley, John; Zhong, Jiemign; Chen, Songhua; Sun, Qiang; Wang, Xiaoming
Abstract: Objective: To report care pathways of tuberculosis (TB) patients under the integrated model, where TB clinical service is provided by a general hospital instead of the TB dispensary, with the aim of providing policy recommendations for TB care reforms in China. Methods: Six counties implementing the integrated model were randomly selected, and 50 TB patients in each county participated in a questionnaire survey. Results: Of the 301 participants, 82 visited only the TB designated hospital. A patient visited a median of two health providers in total. The median external provider delay and internal provider delay were 1 and 0 day, respectively. The median out‐of‐pocket medical costs were US$379 in total; US$293 in the TB units and US$0 in other health units in the TB designated hospital. Logistic regression analyses suggested that patients who visited the primary care facilities first tended to have longer external delays (OR = 5.71) than patients who visited the other hospitals (OR = 10.16). Conclusion: The integrated model is promising as it reported relatively fewer patient pathways and shorter delays than the dispensary model. However, the integrated model did not reduce patient out‐of‐pocket costs.